Influence of Aggregates in Concrete on Fiber-Optic Based Thermal Integrity Profiling Analysis of Concrete Structures - Zhong, Ruoyu; Deng, Wen (Frontiers in Materials, 2020)
Fiber-optic sensor has drawn wide attention in the nondestructive testing and evaluation of civil engineering materials due to its high accuracy and resolution as well as cost-efficiency. Currently, using optical fiber as the temperature sensor is proposed to conduct the thermal integrity profiling (TIP) of concrete structures. However, concrete is not a thermally homogeneous material as assumed in current studies of concrete TIP. Its essential components, such as aggregates may cause thermal inhomogeneity problems when implementing fiber-optic sensors for TIP. In this paper, we use the concrete structures with different grades of aggregates to conduct numerical simulation for nondestructive thermal testing. The goal is to investigate how the thermal inhomogeneity caused by aggregates would influence the testing result. Firstly, we establish three concrete structure models with three different grades of aggregates based on the scenarios where these concrete structures will be used. Then, we numerically simulate the thermal process on these models and extract the temperature at the location where optical fiber would be installed. The influence caused by the inhomogeneity of aggregate size and distribution as well as the possible method to minimize the effect are evaluated in the paper. Overall, aggregates of concrete have a significant influence on the accuracy of TIP analysis, and defects could be veiled if no proper treatment to the data is implemented for TIP analysis.